The Reception of Debussy in the Stockholm Press up to 1926 - Edling, Anders (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2013)
The first reviews studied here were written after the Stockholm premieres of Debussy’s String Quartet and the Prélude à l’Après-midi d’un faune in 1906, and the last ones after the premiere of Pelléas et Mélisande in 1926. In 1906 and the following years, Debussy was treated as an avant-gardist in the Swedish press; many critics were provoked, but others, such as Ture Rangström and Sigurd von Koch, were enthusiastic. The idea of Debussy being passé was introduced already in 1915, and was more often expressed after World War I, especially in the reviews of Pelléas et Mélisande written by Moses Pergament and Wilhelm Peterson-Berger. Hugo Riemann’s notion that Debussy systematically used certain harmonics, such as the 11th and 13th, to achieve his typical effects was very much embraced by the Swedish critics in general, and they also often relied on Romain Rolland’s judgements on the composer.